2014
DOI: 10.1063/1.4902520
|View full text |Cite
|
Sign up to set email alerts
|

Defect-free ZnO nanorods for low temperature hydrogen sensor applications

Abstract: Uniformly distributed and defect-free vertically aligned ZnO nanorods (NRs) with high aspect ratio are deposited on Si by sputtering technique. X-ray diffraction along with transmission electron microscopy studies confirmed the single crystalline wurtzite structure of ZnO. Absence of wide band emission in photoluminescence spectra showed defect-free growth of ZnO NRs which was further conformed by diamagnetic behavior of the NRs. H2 sensing mechanism based on the change in physical dimension of channel is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…The crystalline nature of the ZnO is an important factor to realize the pyro‐phototronic effect. Thus, X‐ray diffraction (XRD) measurements and analysis were performed, which confirmed the formation of high‐quality wurtzite ZnO (see Figure b) . In fact, the θ–2θ scan revealed two main peaks at 34.26° and 31.48°, corresponding to the (002) and (100) planes, respectively; this also confirmed the purity of the deposited oxide and matches well to the literature (JCPDS card no 36‐1451).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The crystalline nature of the ZnO is an important factor to realize the pyro‐phototronic effect. Thus, X‐ray diffraction (XRD) measurements and analysis were performed, which confirmed the formation of high‐quality wurtzite ZnO (see Figure b) . In fact, the θ–2θ scan revealed two main peaks at 34.26° and 31.48°, corresponding to the (002) and (100) planes, respectively; this also confirmed the purity of the deposited oxide and matches well to the literature (JCPDS card no 36‐1451).…”
Section: Resultssupporting
confidence: 82%
“…Thus, X-ray diffraction (XRD) measurements and analysis were performed, which confirmed the formation of high-quality wurtzite ZnO (see Figure 1b). [24,25] In fact, the θ-2θ scan revealed two main peaks at 34.26° and 31.48°, corresponding to the (002) and (100) planes, respectively; this also confirmed the purity of the deposited oxide and matches well to the literature [26] (JCPDS card no 36-1451). In addition, the crystalline size (D) corresponding to the dominating (002) peak was calculated using the Scherrer equation:…”
Section: Schematics X-ray Diffraction Device Transmittance and Orisupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, the conduction of ZnO nanorods is correlated with cross section and given as follow 44 ,where G, n, e, l, and µ are electrical conductivity, electron concentration, length of NR and electron mobility, respectively. Fast oxygen desorption will take place when ZnO NRs are exposed to hydrogen and increase the conduction cross section channel area.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, low operating temperature with low level of gas detection using ZnO based nanostructure is prime goal for many researchers. Ranwa et al 25 fabricated ZnO NRs/Si Schottky heterojunction based hydrogen sensor which showed fast response time $21.6 s at low operating temperature ($70 C) in pure hydrogen gas. Das et al 26 fabricated Pt/ZnO single nanowire Schottky diode by using e-beam lithography.…”
Section: Introductionmentioning
confidence: 99%